Alternative Media: Theories, Conceptual Frameworks, and Critical Perspectives - Dura, Yam Bahadur (Journal of Productive Discourse, 2025)
This thematic paper critically examines the diverse theoretical frameworks and conceptualizations of alternative media, tracing its evolution from traditional forms to contemporary digital platforms. Drawing on critical communication studies, social movement theory, participatory media approaches, and radical media theories, it explores how scholars such as John Downing, Clemencia Rodríguez, and Chris Atton define alternative media in relation to power structures, media activism, participatory communication, and community engagement. By analyzing these key theoretical perspectives, this paper highlights the distinct characteristics that differentiate alternative media from its mainstream counterparts, considering factors such as ownership, content, distribution, and audience engagement. The findings emphasize the evolving nature of alternative media in the digital era, where decentralized platforms challenge mainstream narratives and create new spaces for grassroots communication. They also underscore the need for further research on the sustainability and impact of alternative media in contemporary society, particularly with the growing demand for more academic discourse on this topic in Nepal.